Patients' and Therapists' Views of Integrated Online CBT for Depression - Fiona Fox; Nicola Wiles; David Kessler; Debbie Tallon; Laura Thomas; Christopher Williams; Roz Shafran; Paul Lanham; Katrina Turner (Wiley, 2024)
Abstract Background CBT is an effective treatment for depression, but access varies across the United Kingdom. Online CBT increases access. The INTERACT platform was designed to support patient engagement in CBT, enabling therapists to deliver high‐intensity CBT via typed instant messaging and allowing patients and therapists access to an integrated online library of resources during and between sessions. Methods The INTERACT trial aimed to evaluate this integrated approach to delivering CBT for primary care patients with depression. A nested qualitative study was conducted within the trial. Interviews were conducted with 20 patients who received the intervention, 9 therapists who delivered it and 3 therapist supervisors. Data were analysed using thematic analysis. Results The combination of receiving support from a therapist and having access to integrated online CBT resources enabled patients to better manage their depression. Platform benefits included the opportunity to review transcripts to clarify how to complete homework tasks and track progress in managing their depression. The typing process allowed reflection and a focused discussion. However, less could be covered than during an in‐person session, which reduced therapists' expectations around goal setting. Patients who did not complete therapy struggled with the typing and found the CBT approach too demanding. Conclusion Findings highlight the importance of establishing patient and therapist goals and expectations about what can be achieved in CBT mediated by typing. Some patients are comfortable communicating via typing and are motivated to utilise online resources in between sessions. Exploring the benefits and challenges of typed CBT with patients will enable them to make an informed choice about referral for this novel approach to therapy. Patient or Public Contribution Patients, service users and members of the public were involved in the study design and management. Substantial pilot work gathered stakeholder feedback and informed the design of the intervention, before undertaking the RCT. Coauthor P.L. is a service user representative co‐applicant and member of the management group responsible for developing the intervention and the trial. Two PPI members sit on the Independent Steering Committee. PPI members provided valuable feedback on the study resources and documents.